SUPPORTING THE STUDENTS’ UNDERSTANDING OF PERCENT BY USING GRID 10 X 10 - SISKA NINGSIH; RATU ILMA INDRA PUTRI; ELY SUSANTI (Sriwijaya University Learning and Education International Conference, 2016)
Percent is often used in a variety of media in everyday life. Percent begins to be studied at theelementary level. Students are more or less know about percent, but they are often difficulties inpercent problems. This study aims to support students’ understanding in learning percent using a grid10 x 10 and Indonesian Realistic Mathematics Education (PMRI) approach. The method used isdesign research of type validation studies. Design research consisted of three stages: preliminary,design experiments and retrospective analysis. This research was conducted in SD Negeri 23 OKU byinvolving students of class V. The data were collected through video recordings, students’ work,interviews and then analyzed the data mostly in qualitative ways. The results of this study are learningtrajectory that consists of 3 activities and shows that the grid of 10 x 10 with PMRI approach can helpstudents understand the learning percent.